2017
DOI: 10.1002/ajcp.12124
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Premature Match Closure in Youth Mentoring Relationships

Abstract: Although mentoring is a popular and effective means of intervention with youth, the positive effects of mentoring can be diminished by premature match closure of relationships. Program, mentor, and mentee characteristics were examined as predictors of premature match closure. Secondary data analyses were conducted on a large national database of mentoring programs consisting of match and youth risk information from 170 mentoring programs and 6468 matches from across the U.S. Premature closure was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
75
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 52 publications
(86 citation statements)
references
References 36 publications
6
75
3
Order By: Relevance
“…A few studies have examined program experiences in relation to mentoring relationship quality, but not youth risk. For instance, mentor training, communication and support have been positively associated with relationship quality, youth outcomes, and the continuation of relationships (DuBois, Holloway, Valentine, & Cooper, ; Herrera et al., ; Kupersmidt, Stump, Stelter, & Rhodes, ; McQuillin, Straight, & Saeki, ; Stelter, Kupersmidt, & Stump, ). Because program experiences may be more amendable than mentor/mentee characteristics, they may be important factors to consider in buffering the negative impact of youth risk on the quality of the mentoring relationship.…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have examined program experiences in relation to mentoring relationship quality, but not youth risk. For instance, mentor training, communication and support have been positively associated with relationship quality, youth outcomes, and the continuation of relationships (DuBois, Holloway, Valentine, & Cooper, ; Herrera et al., ; Kupersmidt, Stump, Stelter, & Rhodes, ; McQuillin, Straight, & Saeki, ; Stelter, Kupersmidt, & Stump, ). Because program experiences may be more amendable than mentor/mentee characteristics, they may be important factors to consider in buffering the negative impact of youth risk on the quality of the mentoring relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the benefits of match longevity, premature match closure has been found in 30% to 50% of all formal mentoring relationships (DeWit et al., ; Kupersmidt, Stump, Stelter, & Rhodes, ) and premature closure is related to negative youth outcomes (Grossman & Rhodes, ; Herrera, Grossman, Kauh, Feldman, & McMaken, ; Spencer, ). Mentees who experience premature match closure can experience feelings of disappointment, guilt, anger, shame, and abandonment (Karcher, ).…”
Section: Introductionmentioning
confidence: 99%
“…Mentor characteristics such as age, work experience in a helping profession, marital status, and level of income have been shown to predict premature closure (DuBois, Holloway, Valentine, & Cooper, ; Grossman & Rhodes, ; Kupersmidt, Stump, et al., ). In addition, mentors with extremely high positive expectations can experience feelings of discouragement and frustration when they perceive a lack of improvement in their mentees or their mentoring relationships, which may result in their ending the mentoring relationship abruptly or prematurely (Madia & Lutz, ; Spencer, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are several ways in which a close and supportive mentoring relationship may affect maltreated children's coping. Although several studies have found that family risk factors including placement in foster care and poor relationships with parents are associated with early termination of mentoring relationships (DeWit et al., ; Kupersmidt, Stump, Stelter & Rhodes, ; Raposa, Rhodes & Herrera, ), it is hypothesized that the close, relational bond formed between a mentor and child may act as a corrective attachment experience (Rhodes, Grossman & Resch, ; Rhodes, Reddy, Roffman & Grossman, ; Spencer, ). Arguably, if a child who has experienced maltreatment is able to form a high‐quality relationship with their mentor, this relationship may buffer the negative effects of a poor relationship with the biological parent on child coping.…”
Section: Engagement and Disengagement Copingmentioning
confidence: 99%